The Role of A Judge’s Conscience in Deciding Criminal Cases: Practice of Criminal Justice in Indonesia - Antonius Sudirman; Konstantinus Bahang; Joel Casimiro Pinto (Journal of Law and Legal Reform, 2025)
As the leading actor in the criminal justice system in Indonesia, a judge must engage in a dialogue with their conscience before deciding on a criminal case to ensure true justice for all parties. This article aims to analyze the functioning of judges’ consciences in their decisions within the criminal justice system in Indonesia. Therefore, a literature study was conducted. Data is collected by reading and tracing various relevant documents. Furthermore, the data were analyzed using descriptive qualitative methods. The results are as follows: first, conceptually, judges who have a conscience are constantly in dialogue with their consciences, and then they decide cases according to their sincere consciences. Second, in the context of criminal justice in Indonesia, judges are obligated to heed the promptings of their conscience every time they decide on a criminal case. This is because the ultimate goal of criminal justice is to uncover the truth and ensure justice for all parties, namely society, victims, and perpetrators of crimes. However, in fact, there are still judges who disregard their conscience and are easily influenced by extrajudicial powers, such as mass pressure and political interests. For this reason, it is necessary to submit several recommendations: (1) all parents should teach their children the importance of a simple, honest, committed, and responsible life because the family is a cell of society, a place for seedling law enforcement officials, including judges; (2) optimizing the role of the judicial commission in the form of policy support and adequate funds so that the institution can recruit prospective judges and professionally supervise the behavior of judges; (3) Judges who are involved in moral violations or abuse of power are subject to severe criminal sanctions to create a deterrent effect.